2018
DOI: 10.1016/j.neuroimage.2018.06.074
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful inhibition: Exploring the role of meaning and modality in response inhibition

Abstract: We frequently guide our decisions about when and how to act based on the meanings of perceptual inputs: we might avoid treading on a flower, but not on a leaf. However, most research on response inhibition has used simple perceptual stimuli devoid of meaning. In two Go/No-Go experiments, we examined whether the neural mechanisms supporting response inhibition are influenced by the relevance of meaning to the decision, and by presentation modality (whether concepts were presented as words or images). In an on-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

8
2

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 77 publications
1
36
0
Order By: Relevance
“…This evidence is consistent with existing fMRI and transcranial magnetic stimulation (TMS) research showing that regions of the PFC and parietal lobe are activated during tasks of inhibitory control in both adults and children (Bunge et al, 2002;Cope et al, 2020;Durston et al, 2002Durston et al, , 2006Tamm et al, 2002;van Belle et al, 2014). Specifically, the right dorsolateral prefrontal cortex (DLPFC; Casey et al, 1997;Cope et al, 2020;Durston et al, 2006), the right inferior frontal cortex (as part of a fronto-basal-ganglia network; Aron et al, 2004Aron et al, , 2014Bari & Robbins, 2013;Chambers et al, 2009;Chikazoe, 2010), and regions within the right parietal cortex (Bunge et al, 2002;Chikazoe et al, 2009;Cope et al, 2020;Durston et al, 2002;Gonzalez Alam et al, 2018;Mehnert et al, 2013;Osada et al, 2019) are reliably found to be active in tasks requiring response inhibition. Some studies have also found activation in the bilateral orbito-frontal when response inhibition is needed (Casey et al, 1997;Cope et al, 2020;Rubia et al, 2006;Tamm et al, 2002).…”
supporting
confidence: 78%
“…This evidence is consistent with existing fMRI and transcranial magnetic stimulation (TMS) research showing that regions of the PFC and parietal lobe are activated during tasks of inhibitory control in both adults and children (Bunge et al, 2002;Cope et al, 2020;Durston et al, 2002Durston et al, , 2006Tamm et al, 2002;van Belle et al, 2014). Specifically, the right dorsolateral prefrontal cortex (DLPFC; Casey et al, 1997;Cope et al, 2020;Durston et al, 2006), the right inferior frontal cortex (as part of a fronto-basal-ganglia network; Aron et al, 2004Aron et al, , 2014Bari & Robbins, 2013;Chambers et al, 2009;Chikazoe, 2010), and regions within the right parietal cortex (Bunge et al, 2002;Chikazoe et al, 2009;Cope et al, 2020;Durston et al, 2002;Gonzalez Alam et al, 2018;Mehnert et al, 2013;Osada et al, 2019) are reliably found to be active in tasks requiring response inhibition. Some studies have also found activation in the bilateral orbito-frontal when response inhibition is needed (Casey et al, 1997;Cope et al, 2020;Rubia et al, 2006;Tamm et al, 2002).…”
supporting
confidence: 78%
“…Consequently, it has been proposed that visual responses in lateral occipital cortex are largely context and task invariant (Bracci et al, 2017;Bugatus et al, 2017;Xu, 2018aXu, , 2018b. However, lateral occipital cortex is also commonly-activated across multiple control-demanding tasks, and by this definition, forms part of the MDN (Waskom et al, 2014;Gonzalez Alam et al, 2018;Hebart et al, 2018). Behavioural goals directly impact object representations in this region (Harel et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, there also appear to be anatomical differences between these networks: regions supporting semantic control extend into more anterior areas of left inferior frontal gyrus, and posterior middle temporal areas, which are not implicated in executive control more generally. Moreover, SCN shows strong left-lateralisation, in contrast to other aspects of control, which are bilateral or even right-lateralized (Gonzalez Alam et al 2018; Gonzalez Alam et al 2019; Jefferies et al 2020).…”
Section: Introductionmentioning
confidence: 88%